Square-wave anodic-stripping voltammetric determination of Cd, Pb and Cu in a hydrofluoric acid solution of siliceous spicules of marine sponges (from the Ligurian Sea, Italy, and the Ross Sea, Antarctica). - TRUZZI, Cristina; ANNIBALDI, Anna; ILLUMINATI, Silvia; SCARPONI, Giuseppe; E. BASSOTTI (Analytical and Bioanalytical Chemistry, 2008)
Square-wave anodic-stripping voltammetry (SWASV) was set up and optimized for simultaneous determination of cadmium, lead, and copper in siliceous spicules of marine sponges, directly in the hydrofluoric acid solution (~0.55 mol L−1 HF, pH ~1.9). A thin mercury-film electrode (TMFE) plated on to an HF-resistant epoxy-impregnated graphite rotating-disc support was used. The optimum experimental conditions, evaluated also in terms of the signal-to-noise ratio, were as follows: deposition potential −1100 mV vs. Ag/AgCl, KCl 3 mol L−1, deposition time 3–10 min, electrode rotation 3000 rpm, SW scan from −1100 mV to +100 mV, SW pulse amplitude 25 mV, frequency 100 Hz, ΔEstep 8 mV, tstep 100 ms, twait 60 ms, tdelay 2 ms, tmeas 3 ms. Under these conditions the metal peak potentials were Cd −654±1 mV, Pb −458±1 mV, Cu −198±1 mV. The electrochemical behaviour was reversible for Pb, quasi-reversible for Cd, and kinetically controlled (possibly following chemical reaction) for Cu. The linearity of the response with concentration was verified up to ~4 μg L−1 for Cd and Pb and ~20 μg L−1 for Cu. The detection limits were 5.8 ng L−1, 3.6 ng L−1, and 4.3 ng L−1 for Cd, Pb, and Cu, respectively, with td=5 min. The method was applied for determination of the metals in spicules of two specimens of marine sponges (Demosponges) from the Portofino natural reserve (Ligurian Sea, Italy, Petrosia ficiformis) and Terra Nova Bay (Ross Sea, Antarctica, Sphaerotylus antarcticus). The metal contents varied from tens of ng g−1 to ~1 μg g−1, depending on the metal considered and with significant differences between the two sponge species.